The entrepreneurial skills and strategies of students in Mathematics and Science courses - Carbonel, Loneza G.; Doctor, Joy Grace P.; Agbisit, Imelda C. (2019)
This paper dealt with the different strategies of promoting entrepreneurial skills to the students in the field of Science and Mathematics. It also identified the skills needed in pursuing Science and Mathematics courses. This descriptive research included 90 students taking Science and Mathematics subjects in the College of Liberal Arts. the study found out the respondents' strong agreement on the different strategies used in the promotion of entrepreneurial skills, which include encouraging them to be resilient, risk-taker, persistent and had working. Teachers are encouraged to teach Mathematics and Science students using the following strategies: using the questioning method, writing assignments, leading students to think critically, scientific knowledge-based learning, decision-making through correct reasoning, and participating actively and science and mathematics activities. It also revealed that the different skills needed entrepreneurial activities are the ability to solve problems to learn and act independently, to plan a solution, to analyze and plan further action, to set goals and act creatively, to assess and classify information, to take the initiative and responsibility, and to cooperate and work in a team.
Keywords: Entrepreneurial competency